Histochemical Techniques in Plant Science: More Than Meets the Eye. (17th February 2021) - Yadav, Vaishali; Arif, Namira; Singh, Vijay Pratap; Guerriero, Gea; Berni, Roberto; Shinde, Suhas; Raturi, Gaurav; Deshmukh, Rupesh; Sandalio, Luisa M; Chauhan, Devendra Kumar; Tripathi, Durgesh Kumar
Abstract: Histochemistry is an essential analytical tool interfacing extensively with plant science. The literature is indeed constellated with examples showing its use to decipher specific physiological and developmental processes, as well as to study plant cell structures. Plant cell structures are translucent unless they are stained. Histochemistry allows the identification and localization, at the cellular level, of biomolecules and organelles in different types of cells and tissues, based on the use of specific staining reactions and imaging. Histochemical techniques are also widely used for the in vivo localization of promoters in specific tissues, as well as to identify specific cell wall components such as lignin and polysaccharides. Histochemistry also enables the study of plant reactions to environmental constraints, e.g. the production of reactive oxygen species (ROS) can be traced by applying histochemical staining techniques. The possibility of detecting ROS and localizing them at the cellular level is vital in establishing the mechanisms involved in the sensitivity and tolerance to different stress conditions in plants. This review comprehensively highlights the additional value of histochemistry as a complementary technique to high-throughput approaches for the study of the plant response to environmental constraints. Moreover, here we have provided an extensive survey of the available plant histochemical staining methods used for the localization of metals, minerals, secondary metabolites, cell wall components, and the detection of ROS production in plant cells. The use of recent technological advances like CRISPR/Cas9-based genome-editing for histological application is also addressed. This review also surveys the available literature data on histochemical techniques used to study the response of plants to abiotic stresses and to identify the effects at the tissue and cell levels.